The Influence of Leadership and Supervision on Work Discipline with Commitment as an Intervening Variable (Study at the Grobogan Regency Industry And Trade Office) - Dedy Restu Nugroho; Wyati Saddewisasi; Ardiani Ika Sulistyawati (Eduvest - Journal of Universal Studies, 2025)
One of the main keys to determining the success of an organization in achieving goals is employee work discipline. A high level of work discipline reflects the employee's commitment and responsibility to the existing regulations. However, many employees have proven to be less than optimal in implementing employee discipline rules. There are many factors that can affect the lack of work discipline among employees. This study aims to determine the influence of Leadership and Supervision on Work Discipline with Commitment as an intervening variable in employees of the Grobogan Regency Disperindag, with a population of 57 ASN employees, sampling 55 ASN (PNS and PPPK) using the census method. The data collection method in this study uses a questionnaire and a data collection scale with a Likert scale. The analysis technique used in this study employs SEM (Structural Equation Model) with the Partial Least Square (PLS) analysis technique operated using the help of SmartPLS software version 3.0. The results of the study show that Leadership has a positive and significant effect on Commitment; Supervision has a positive and significant effect on Commitment; Commitment has a positive and significant effect on Work Discipline; Leadership does not have a significant effect on Work Discipline; and Supervision does not have a significant effect on Work Discipline. In addition, Leadership has a positive effect on Work Discipline through Commitment, and Supervision has a significant effect on Work Discipline through Commitment.